2017
DOI: 10.21020/husbfd.321328
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Causes Affecting Inhalants Addiction in Children and Adolescents: Case Report

Abstract: ÖzetUçucu maddelerin sanayi sektöründeki işlevselliği dışında keyif verici, uyarıcı ve haz alıcı olarak kötüye kullanımı yaygınlaşmaktadır. Son yıllarda uçucu madde bağımlılığı çocuk ve ergenler arasında hızla yayılmaktadır. Ayrıca çocuk ve ergenlerin madde kullanma sebepleri de değişkenlik göstermektedir. Bağımlılığın görülme sıklığı ortalama 14-15 yaşlarındaki hastalardadır. Uçucu madde bağımlılığını etkileyen psikolojik nedenlere bakıldığında, genelde stresle nasıl baş edileceğinin bilinmemesi, olumsuz ve k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Consequently, problems related to these children and their substance misuse are frequently discussed in the media [33]. Young people learn about the effects of inhalants and may experiment with these substances to cope with certain problems [34]. While Turkey has long been a well-known drug trafficking route, particularly for heroin, domestic drug use has become a significant problem in recent decades [5,35].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, problems related to these children and their substance misuse are frequently discussed in the media [33]. Young people learn about the effects of inhalants and may experiment with these substances to cope with certain problems [34]. While Turkey has long been a well-known drug trafficking route, particularly for heroin, domestic drug use has become a significant problem in recent decades [5,35].…”
Section: Discussionmentioning
confidence: 99%
“…The existence of thoughts that alcohol facilitates social relations causes the person to start using alcohol more easily and earlier. Moreover, it is observed that curiosity, wannabe, and modelling family members who drink are risk factors for starting alcohol in children and adolescents (Karaaslan 2017). In a study conducted with Danish adolescents, the relationship between sociocultural and school-related risk factors and alcohol consumption of 1453 15-year-old students was examined.…”
Section: Sociocultural Factorsmentioning
confidence: 99%